Toward an understanding on father involvement in divorced families - Diniz, E. (2020)
Important changes regarding the traditional family structure and the beliefs about gender roles, more specifically about the parental roles, have contributed to an increasing number of studies focusing on the father and his involvement in the family, especially with the child. However, research is still scarce among divorced families. Therefore the main goal of this study was to analyze father involvement with their children (one child per family) in divorced Portuguese parents. Sociodemographic variables such as parents’ age, education and the child’s sex were considered. Fathers (N = 118) reported on their involvement regarding the child. Results show that the father’s involvement varies according to the type of activities and was moderated by the child’s sex and the mother’s education. Fathers were more involved in indirect care and outdoor leisure activities with their sons than daughters, also father involvement in outdoor leisure increased in families in which the mother’s education was higher. These results are important to understand father involvement as a multidimensional construct, and how it’s affected by parents and child’s characteristics, particularly after divorce.